CALCULATIONS OF THE SUITABILITY OF FOOD INDUSTRY WASTEWATER FOR BIOLOGICAL TREATMENT - Bublienko, Наталія; Salavor, Оксана; Togachynska, Ольга; Nychyk, Оксана (Biota. Human. Technology, 2025)
Objective. Determination of pollution indicators of wastewater of various origins and calculations of their suitability for biological treatment of a certain type. Methodology. The research was conducted by analyzing the level of pollution of wastewater of the III category of a sugar factory and the total effluent of a city dairy. Determination of pollution indicators of wastewater (COD, BOD, total nitrogen, phosphorus, etc.) was carried out in the ecological laboratory of the Department of Ecology and Ecomanagement of the National University of Food Technologies using standard methods. Laboratory installations were used to carry out the purification processes: aeration tank, methane tank, gasholder. Scientific novelty. The study reveals the features of calculations regarding the suitability of wastewater of specific food industry enterprises for a certain method of biological treatment. The use of the calculations will ensure the selection of the optimal wastewater treatment technology, which will be economically and environmentally justified. This will optimize and accelerate the choice of the method of wastewater treatment. Conclusions. The initial parameters of the III category wastewater of the sugar factory and the total wastewater of the city dairy were studied. Calculations proved the suitability of the III category wastewater of the sugar factory for biological treatment under anaerobic conditions: with a ratio of BODtotal to COD equal to 0,76; with a COD indicator exceeding 2000 mg O/dm3; with a ratio of BODtotal to biogenic elements 464,7:7,12:1; with an optimal pH of 7,4 and the absence of toxic elements. The wastewater of the city dairy is suitable for aerobic biological treatment: with a ratio of BODtotal to COD equal to 0,81; with a COD indicator not exceeding 2000 mg O/dm3; with a ratio of BODtotal to biogenic elements 96,3:5,04:1; optimal pH 6,8 and the absence of toxic elements. Methane fermentation of sugar factory wastewater resulted in high purification efficiency – 94,23 %. The amount of biogas was 0,923 dm3/g COD, the methane content in it – 66 %. Aerobic biological purification of dairy wastewater ensured purification efficiency – 96,88 %.